Photodynamic Therapy in the treatment of oral lesions in patients with COVID-19 in the ICU: Two case reports (Research, Society and Development, 2022)
Patients admitted to intensive care units (ICUs) who suffers from COVID-19 in a serious and/or critical condition are susceptible to several manifestations that can be fatal or generate long-term sequelae. Oral complications were observed and the hypotheses about their etiology suggest that they are due to infection by the SARS-CoV-2 it self or secondary manifestations of the patient's systemic condition, being necessary more research at a multidisciplinary level for further discoveries related to etiopathogenesis of these manifestations. The purpose of this study was to evaluate and describe oral lesions presented by two patients admitted to the Intensive Care Unit with COVID-19 at a University Hospital treated with photodynamic therapy (aPDT). Patients were evaluated by a dentist who performed treatment of the lesions using the aPDT technique and associated therapies for control and remission of alterations. In view of the report, it was possible to conclude that Photodynamic Therapy is effective in the treatment of alterations in the mouth when correctly indicated, evidencing the importance of the dentist in a hospital environment inserted in a multiprofessional team to perform the diagnosis and treatment of oral alterations.